(untitled) (Ustozlar uchun, 2025)
This article examines how the results of international assessments such as PISA, TIMSS, and PIRLS can be effectively used to improve the educational process. It highlights how assessment data supports curriculum development, enhances teaching methods, and helps identify students’ learning gaps. The study emphasizes the importance of using international benchmarks to strengthen teacher professionalism and promote data-driven decisions in schools.